Assessment of stability of a revitalized stream T12 in Orlické Záhoří - Jana Marková; Petr Pelikán (Acta Universitatis Agriculturae et Silviculturae Mendelianae Brunensis, 2013)
The aim of presented project is to execute an analysis and evaluation of stream-bed conditions for streams after revitalisation measures. Revitalisation of stream T12 in Orlické Záhoří has been comprehensive, included changes of stream line and longitudinal and transversal profile. The evaluation was so provided in two absolutely different stream-beds. The evaluation was focused on stream-bed ground and slopes stability, which were established on the base of tangential stress, scouring and nonscouring velocity and of mean velocity in vertical calculation. Then the individual methods of calculation were compared and the results were faced with actual status of stream-bed and supposed development of stream-bed morphology.